2005
DOI: 10.1577/m04-077.1
|View full text |Cite
|
Sign up to set email alerts
|

Initial Predation of Stocked Fingerling Largemouth Bass in a Texas Reservoir and Implications for Improving Stocking Efficiency

Abstract: We assessed the importance of initial predation as a source of mortality of stocked fingerling Florida largemouth bass Micropterus salmoides floridanus (30–46 mm total length). Florida largemouth bass were tagged with coded wire tags and stocked (3,000 fish/site) at six sites in Elm Creek Embayment of O. H. Ivie Reservoir, Texas—the location of an earlier study in which the immediate mortality of stocked fish was found to be highly variable. Stocked fish were eaten by at least five species of predators that va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
2
26
1
Order By: Relevance
“…Buckmeier et al (2005) found predation contributed up to 27% of initial mortality within the first 12 h of stocking fingerling largemouth bass in O. H. Ivie Reservoir, Texas. Predation was not measured in the present study; however, it has been suggested that fish weakened by hunger are more likely to fall victim to predation (Brown and Laland 2001), and unlearned foraging behavior may have indirectly contributed to predation of hatchery-reared fish.…”
Section: Discussionmentioning
confidence: 93%
“…Buckmeier et al (2005) found predation contributed up to 27% of initial mortality within the first 12 h of stocking fingerling largemouth bass in O. H. Ivie Reservoir, Texas. Predation was not measured in the present study; however, it has been suggested that fish weakened by hunger are more likely to fall victim to predation (Brown and Laland 2001), and unlearned foraging behavior may have indirectly contributed to predation of hatchery-reared fish.…”
Section: Discussionmentioning
confidence: 93%
“…Contrary to our expectation, we did not find a direct relationship between the recapture rate and the stocking season in pikeperch. This is surprising because size-dependent winter mortality of juveniles is one of the key factors in year-class strength formation of pikeperch (Ruuhijärvi et al, 1996;Lappalainen et al, 2000) and closely related walleye Sander vitreus (Johnson et al, 1996), and is likely to be even more important in freshly stocked fish which need to spend extra energies for foraging appropriate habitat in unknown environment (Bolland et al, 2009;Buckmeier et al, 2005). Accordingly, several studies on different species concluded that fish stocked in spring and summer have better chance to survive, and thence to be recaptured, than those released just before the winter (Templeton, 1971;Strange and Kennedy, 1979;Kennedy et al, 1982;Vostradovsky, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented domestication effects in M . floridanus including poor foraging skills (Porak et al ., ; Wintzer & Motta, ; Pouder et al ., ), reduced anti‐predatory behaviour (Buckmeier et al ., ) and increased movement after release (B. Thompson, pers. comm., 2014).…”
Section: Introductionmentioning
confidence: 99%